PATRIARCHY AND WOMEN’S SUBORDINATION: STUDY OF NYAI ONTOSOROH IN PRAMOEDYA ANANTA TOER’S THIS EARTH OF MANKIND” - mei handayani (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
This study analyzes patriarchy and women's subordination in the Novel “This Earth of Mankind” written by Pramoedya Ananta Toer. Colonialism brought patriarchal status and women's subordination to indigenous women, while patriarchy gave women the lowest authority and authority. Nyai Ontosoroh is a native Javanese woman; her husband is Dutch, who lived and was part of the Dutch colonialism. She was a mistress who sold to Dutch shows. This study aimed to explore the patriarchal status and subordination of women during the Dutch colonial era described by Nyai Ontosoroh in Pramoedya Ananta Toer's novel “This Earth of Mankind” and to reveal the patriarchal and female factors that occur in the protagonist in this novel. The data source is the historical novel by Pramodedya Ananta Toer entitled "This Earth of Mankind." The research analysis was carried out using the theoretical concept of feminism, which states that patriarchy is a term used to determine the subordination status of women. The findings revealed that throughout the Dutch colonial era, Nyai Ontosoroh encountered patriarchy and women's perceptions toward the law. The study also reveals that the Dutch are affected by factors that might still contribute to patriarchy and women. Despite the fact that Nyai Ontosoroh has repeatedly disobeyed Dutch law, she is simply an indigenous woman who is subjected to a patriarchal and subordinate system that has nothing to do with Dutch colonization. As a result, she was treated unfairly and was forced to submit to Dutch authority, which lost both her business and her daughter. Keywords: patriarchy, women’s subordination, this earth of mankind